Pengaruh Pemberian Minuman Energi Terhadap Kadar Serum Kreatinin Rattus Norvegicus - Budi Santo; Dorta Simamora (Universitas Wijaya Kusuma Surabaya, 2021)
The energy drink is a beverage that is increasingly being used by the community with the aim to improve work performance, vitality, and concentration. The energy drink is also suspected to affect kidney function. This study aims to determine whether there is influence of various brands of energy drinks (M1, M2, M3, M4) of the serum creatinine levels in male rats Rattus norvegicus.This is a study with randomized post test only control group design. The study used male rats Rattus norvegicus as many as 25 animals that were divided into 5 groups. The control group, the group P1 = M1 energy drinks, group P2 = M2 energy drinks, group P3 = M3 energy drinks, group P4 = M4 energy drinks. The energy drinks were given as many as 2.5 ml / 200 g weight / day for 1 month. Cardiac blood sampling performed to measure the levels of serum creatinine and then the results were analyzed using One-Way Anova to compare the levels of serum creatinine in each group of this study. Results of One-Way Anova test obtained by sig α = 0.000 which means there is significant difference between the treatment group and the control group. It can be concluded that the administration of energy drinks to the Rattus norvegicus would be altered the kidney function. It is caused by various substances contained in energy drinks such as taurine, sugar, vitamin B, caffeine, and other supplementary materials.